It's a wonderful life mentally subtracting positive events improves people's affective states, contrary to their affective forecasts - Minkyung, Koo; Algoe, Sara B.; Wilson, Timothy D.; Gilbert, Daniel T. (The American Psychological Association, 2008)
The authors hypothesized that thinking about the absence of a positive event from one?s life would improve affective states more than thinking about the presence of a positive event but that people would not predict this when making affective forecasts. In Studies 1 and 2, college students wrote about the ways in which a positive event might never have happened and was surprising or how it became part of their life and was unsurprising. As predicted, people in the former condition reported more positive affective states. In Study 3, college student forecasters failed to anticipate this effect. In Study 4, Internet respondents and university staff members who wrote about how they might never have met their romantic partner were more satisfied with their relationship than were those who wrote about how they did meet their partner. The authors discuss the implications of these findings for the literatures on gratitude induction and counterfactual reasoning.